ROLE OF GLYCODELIN IN REGULATION OF MYELOIDDERIVED SUPPRESSOR CELL DIFFERENTIATION - S. A. Zamorina; V. P. Timganova; M. S. Bochkova; K. Yu. Shardina; S. V. Uzhviyuk; P. V. Khramtsov; M. D. Kropaneva; M. B. Rayev (Медицинская иммунология, 2021)
Glycodelin (PP14, PAEP, alpha-2-microglobulin, dimeric glycoprotein with molecular weight of 42 to 56 kDa) is considered as a reproductive tissue receptivity marker. Despite that glycodelin immunosuppressive effects are well-known there still remains uncovered its role in myeloid suppressor cell (MDSC) regulation. MDSC represent the heterogeneous population of immature myeloid cells that acquire suppressor phenotype while inhibiting the immune response under the pathological states. MDSC are known to play an essential role in supporting the immune tolerance in pregnancy and at transplantation. Our hypothesis suggests that glycodelin is capable of inducing the MDSC formation as the level of these cells is elevated during the successful pregnancy, whereas the spontaneous abortion and progression of eclampsia are associated with low circulating glycodelin. Therefore, the aim of the work was to analyze the role of recombinant glycodelin in physiological concentrations in regulation of MDSC differentiation. Peripheral blood mononuclear cells of donor volunteers were separated via centrifugation on density gradient of 1,077 g/cm3 (Ficoll-Hypaque, Sigma-Aldrich) to obtain MDSC generation in vitro. Then cells obtained were cultured in 24-well plate at a concentration of 1 × 106 cell/ml in complete medium with cytokines IL-6 (20 ng/ml), GM-CSF (40 ng/ml) therein for 14 days at 37 °C and 5% CO2. Medium replacement was made by 7th day in culture followed by cytokine re-introduction, and on the 11th day recombinant glycodelin in physiological concentrations (0,2; 2 mkg/ml) was applied while the pharmacological concentration was 50 mkg/ml. The M-MDSC (LinHLA-DRCD33+CD11b+CD14+CD66b- ) and PMN-MDSC (LinHLA-DRCD33+CD11b+CD14- CD66b+) level was evaluated in cultures using flow cytometry (СytoFlexS (Beckman Coulter)) and “R&D Systems” antibodies according to standard protocol. Statistical data processing was realized with GraphPad Prizm software using Friedman test. It was found that glycodelin did not significantly affect cell viability being assessed with flow cytometry (PI). It was revealed that high GdA concentration (50 mkg/ml) being pharmacological did not render significant effect on MDSC differentiation. Meanwhile, glycodelin in concentrations correspanding the healthy pregnancy (0,2; 2 mkg/ml) was stated to increase the MDSC percentage in induced cultures of human mononuclear cells. When analyzing the subsets it was disclosed that this effect was conditioned by the increase in PMN-MDSC level while the M-MDSC level remained significantly unchanged. This result could be interpreted as glycodelin fetoprotective effect as the increase of the PMN-MDSC level is associated with the suppression of the immune response to paternal antigens. The PMN-MDSC level is known to be elevated in peripheral blood of healthy pregnant women at all the stages of pregnancy as compared to nonpregnant subjects whereas the M-MDSC amount remains unaltered. Meanwhile, patients with miscarriage demonstrated more that by 30% lowering in the MDSC amount in blood and endometrium and in I trimester, in particular. During the physiological pregnancy PMN-MDSC accumulate in placenta, but at spontaneous abortion their number is found to be declined. Placental PMN-MDSC efficiently suppress the T-cell response while concurrently polarizing the CD4+ lymphocytes in Th2 phenotype. PMN-MDSC are suggested to play an essential role in inducing and supporting the tolerance to fetal antigens that allows considering these as promising target of therapeutical manipulation in pregnancy complications. As a whole, we have originally demonstrated the GdA effect on MDSC differentiation.